DETERMINANT FACTORS OF QUALITY OF LIFE IN CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS AT SANJIWANI REGIONAL HOSPITAL, GIANYAR AND KLUNGKUNG REGIONAL HOSPITAL - Ni Wayan Sri Wahyuni; Ni Putu Kamaryati; Made Rismawan; Putu Inge Ruth Suantika (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background: Chronic kidney disease significantly affects the personal abilities and quality of life of patients. Patients with chronic kidney failure undergoing hemodialysis are found to have a tendency to experience a decline in quality of life. The purpose of this study was to determine the determinants of the quality of life of chronic kidney failure patients in the hospital. Research Methods: This study is an analytical study with a cross-sectional approach. The sample of the study was 207 patients. The sampling technique used systematic random sampling. Data were collected using a questionnaire then subjected to bivariate and multivariate analysis. Research Results: The results of the bivariate analysis showed that in the physical and mental domains (age, occupation, blood pressure), the domain of kidney disease burden (age, blood pressure), the domain of disease effects (age, blood pressure, duration of hemodialysis) (p <0.05). The results of the multivariate analysis showed that the physical and mental domains with the results (age p<0.001; AOR: 1.035; 95% CI: 0.50-0.263), (occupation p<0.022; AOR: 0.480; 95% CI: 0.257-0.898), (hemoglobin level p<0.045; AOR: 0.485; 95% CI: 0.239-0.983), (duration of hemodialysis p<0.033; AOR: 2.101; 95% CI: 1.061-4.160). Kidney disease burden domain (age p<0.001; AOR: 0.033; 95% CI: 0.004-0.255), (pressure blood p<0.001; AOR: 0.251; 95% CI: 0.115-0.550). Disease effect domain (age p<0.001; AOR: 11.307; 95% CI: 0.020-0.393), (blood pressure p<0.023; AOR: 2.607; 95% CI: 1.006-4.071), (hemodialysis duration p<0.048; AOR: 0.494; 95% CI: 0.168-878). Conclusion: The determinant factors in the physical and mental domains are age, occupation, hemoglobin level, and blood pressure. In the kidney disease burden domain, they are age and blood pressure. In the disease effect domain, they are age, blood pressure, and hemodialysis duration.